If [tex]y(t)=9e^{-5t}[/tex] satisfies the ODE [tex]y'-ky=0[/tex], then
[tex]y'(t)=-45e^{-5t}[/tex]
and substituting into the ODE gives
[tex]-45e^{-5t}-9ke^{-5t}=0\implies k=-5[/tex]
so that the ODE is [tex]y'+5y=0[/tex].
I'm assuming that you're also supposed to determine the initial value [tex]y_0[/tex] given this ODE. You have
[tex]y'+5y=0\implies e^{5t}y'+5e^{5t}y=0\implies(e^{5t}y)'=0\implies e^{5t}y=C\implies y=Ce^{-5t}[/tex]
Given [tex]y(0)=y_0[/tex], you have
[tex]y_0=C[/tex]
but since you already know that [tex]y=9e^{-5t}[/tex], it follows that [tex]C=9[/tex], and in turn that [tex]y_0=9[/tex].